Autonomous Route Planning for UAV-Based 3D Reconstruction - César Gómez Arnaldo; Francisco Pérez Moreno; María Zamarreño Suárez; Raquel Delgado-Aguilera Jurado (Engineering Proceedings, 2025)
This study presents an innovative approach for the autonomous navigation of unmanned aerial vehicles (UAVs) in complex three-dimensional environments. By implementing the Rapidly Exploring Random Tree (RRT) algorithm, the system can efficiently plot safe flight paths that avoid obstacles of varying shapes and sizes. The discussion includes the technical obstacles faced and the strategies employed to overcome them, leading to the successful development of collision-free navigation routes. This foundational work aims to support future projects that will further refine the system through extensive simulations and real-world UAV deployments for tasks such as image capture and structural inspections.